Management of expatriate medical assistance in Mozambique - Vio Ferruccio (BMC, 2006)
Abstract This paper discusses how Mozambique coped with the health system needs in terms of specialized doctors since independence, in a troubled context of war, lack of financial resources and modifying settings of foreign aid. The Ministry of Health (MOH) managed to make up for its severe scarcity of specialist MDs especially through contracting expatriate technical assistance. Different scenarios, partnerships and contract schemes that have evolved since independence are briefly described, as well as self-reliance option possibility and implications. Lessons learned about donor initiatives aimed at contracting specialists from other developing countries are singled out. The issue of obtaining expertise and knowledge in the global market as cheap as possible is stressed, and realistic figures of cost planning are highlighted, as determined by the overall health system necessities and budget limitations.